A tracer study on the perceived impact of leadership of the UP SLIS Student Council to Post-Graduation professional life - Oasan, Jan Paul S. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Studies, such as, employment profiles and more general follow-ups on UP School of Library and Information Studies graduates already exists, but the relation or lack thereof between student council experience with the UP SLIS and post-graduation professional life was yet to be expressed. Perceptions of former UP SLIS student council members on the impact of their former positions on development as individuals towards assuming professional careers, have also gone undocumented.